Paediatric dominant and non-dominant handgrip reference curves and the association with body composition - Catherine M. Avitabile; David R. Weber; Babette S. Zemel (Taylor & Francis Group, 2024)
AbstractBackground Lack of paediatric reference data limits the utility of handgrip strength as a measure of fitness and well-being.Aim To develop paediatric handgrip reference curves and evaluate associations with body size and composition and race/ethnicity group.Subjects and methods Handgrip, body size and composition data were obtained from National Health and Nutrition Examination Survey 2011-2014 participants aged 6-20 years. Densitometry-derived fat and appendicular lean soft tissue mass index Z-scores (FMIZ, ALSTMIZ) were generated in participants >8 years. Dominant and non-dominant handgrip reference curves were created using the LMS method. Analyses included sample weights to produce nationally representative estimates.Results Differences in handgrip strength according to hand dominance increased with age. Handgrip strength was associated with height and arm length Z-scores (R = 0.42 to 0.47) and ALSTMIZ (R = 0.54). Handgrip strength was higher in the non-Hispanic Black group and lower in the Mexican American compared to non-Hispanic White group. Group differences were attenuated when adjusted for height, arm length or ALSTMIZ.Conclusion Paediatric handgrip reference curves were generated from which individual Z-scores can be calculated separately for dominant versus non-dominant hand and adjusted for body size. Association with ALSTMIZ suggests handgrip Z-score may be used as a measure of functional body composition.